Vài suy nghĩ về việc ứng dụng kết quả nghiên cứu ngôn ngữ học xã hội vào thực tiễn ở Việt Nam/Nguyễn Thị Thanh Bình. - Nguyễn, Thị Thanh Bình.
Applying academic result to the real-world has always been one of the major concerns of the social sciences and humanities. This paper outlines some general features of how sociolinguistic insights have been applied to different areas of the social life in Vietnam.Beside the areas that have benefited greatly from sociolinguistic research, the paper also point out some social areas where sociolinguistic insights can also be employed in order to serve the needs of the reality.